Integrating Islamic Law and Customary Law: Codification and Religious Identity in the Malay Buyan Community of Kapuas Hulu - Nordin, Zaimuariffudin Shukri; Ruslan, Ismail; Yusriadi, Yusriadi; Hamzah, Nur; Darmadi, Didi (Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
This article analyzes the integration of Islamic law and customary law in shaping the religious identity of the Malay Buyan community in Kapuas Hulu, West Kalimantan, Indonesia. While Islamic law plays a central role in regulating social and religious life, local customary law remains deeply embedded in the community’s legal consciousness and socio-cultural framework. Previous studies have often treated these two legal systems as separate or even contradictory. However, this study challenges such a dichotomous perspective by demonstrating that Islamic law and customary law engage in an ongoing process of negotiation, resulting in an adaptive and contextually dynamic legal framework. Using a socio-legal approach, this research collects data through in-depth interviews with ten key informants, participant observation, and document analysis. The findings reveal that Islamic law does not replace customary law but is instead integrated into the local legal system, influencing various aspects of social order, family structures, and the sustainable management of natural resources. This integration is evident in the use of Islamic legal terminology, the substance of legal norms, the mechanisms for customary fines, and the role of Islamic religious leaders in the codification of customary law. These findings challenge the prevailing bipolar view that positions Islamic law and customary law as inherently opposing systems. Instead, this study highlights a dynamic and integrative interaction between the two legal traditions, ensuring both social harmony and legal continuity. Ultimately, the article argues that the coexistence of Islamic and customary law is not a source of conflict but a mutually reinforcing and evolving process that contributes to strengthening both religious and cultural identity in a predominantly Muslim society. [Artikel ini menganalisis integrasi hukum Islam dan hukum adat dalam pembentukan identitas keagamaan masyarakat Melayu Buyan di Kapuas Hulu, Kalimantan Barat, Indonesia. Meskipun hukum Islam memiliki peran penting dalam mengatur kehidupan sosial dan keagamaan, hukum adat setempat tetap tertanam kuat dalam kesadaran hukum masyarakat. Penelitian sebelumnya sering kali memperlakukan kedua sistem hukum ini sebagai entitas yang terpisah atau bahkan bertentangan. Namun, studi ini menantang dikotomi tersebut dengan menunjukkan bahwa hukum Islam dan hukum adat terlibat dalam proses negosiasi yang berkelanjutan, sehingga membentuk kerangka hukum yang adaptif dan dinamis sesuai dengan konteks sosial budaya masyarakat. Dengan menggunakan pendekatan sosio-legal, penelitian ini mengumpulkan data melalui wawancara mendalam dengan sepuluh informan kunci, observasi partisipatif, dan analisis dokumen. Temuan penelitian ini menunjukkan bahwa hukum Islam tidak menggantikan hukum adat, tetapi diintegrasikan ke dalam sistem hukum setempat, memengaruhi berbagai aspek tatanan sosial dan budaya, struktur keluarga, serta pengelolaan sumber daya alam secara berkelanjutan. Integrasi ini tampak dalam penggunaan terminologi fikih, substansi norma, mekanisme pembayaran denda adat, serta peran tokoh agama Islam dalam proses kodifikasi hukum adat. Temuan ini menantang pandangan bipolar yang menganggap hukum Islam dan hukum adat sebagai dua entitas yang bertentangan. Sebaliknya, penelitian ini menegaskan bahwa kedua sistem hukum tersebut berinteraksi secara dinamis dan integratif dalam menjaga harmoni sosial dan kontinuitas hukum. Pada akhirnya, artikel ini berargumentasi bahwa koeksistensi hukum Islam dan hukum adat bukanlah sumber konflik, tetapi merupakan proses yang dinamis dan saling memperkuat, yang berkontribusi pada penguatan identitas agama dan budaya dalam masyarakat yang mayoritas beragama Islam.]